Peningkatan Hasil Belajar Pada Sistem Pembelajaran Melalui Model Project Based Learning Berbantuan Platform Zoom Meeting - DIta, Marvinda Rizki (Universitas PGRI Palembang, 2020)
This Classroom Action Study was aimed at describing the online learning outcomes improvement and learning process of Grade V students in SD Negeri 1 Pecangaan Â through projects based learning models with using of Zoom Aplication. The research was conducted through two cycles of action. The diagram shows that the exhaustiveness increased from cycle I at 47% to 88% after cycle II. The learning outcomes also improved from cycle I to II at 63.8 and 82.9 respectively. This study concluded that through the using of Zoom Application, there will be improvement at online learning outcomes in thematic learning.